Highly stable CsPbBr3@SiO2 nanocomposites prepared via confined condensation for use as a luminescent ink. Issue 58 (3rd July 2018) - Cai, Jin; Gu, Kailun; Zhu, Yihua; Zhu, Jingrun; Wang, Yuanwei; Shen, Jianhua; Trinchi, Adrian; Li, Chunzhong; Wei, Gang
Abstract : Stable CsPbBr3 @SiO2 nanocomposites in polar solvents were prepared via an organosilicon ligand-assisted re-precipitation method with polystyrene preventing excessive particle cross-linking and aggregation. Abstract : We have firstly prepared CsPbBr3 @SiO2 nanocomposites with a spherical morphology and diameters less than 125 nm via confined condensation into polystyrene. The obtained CsPbBr3 @SiO2 exhibits high stability in polar solvents and can be used as a solution-processable luminescent ink.